2023
DOI: 10.1007/s11082-023-05161-5
|View full text |Cite
|
Sign up to set email alerts
|

Fresnel diffraction of Humbert beam of type-II by a helical axicon

Abstract: The current study examines the diffraction of Humbert beam of type-II by a helical axicon based on the diffraction integral formula. The considered beam is a new donut beam family which generated by converting the Bessel-Gaussian beams passing through a paraxial ABCD optical system with a SPP. For the diffracted beam produced by the stationary phase approach, we have formulated the intensity distribution. By adjusting the input beam features and the topological charge of the helical axicon, numerical simulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Furthermore, it was recently revealed that, by means of a spiral orthogonal zone plate, one may employ different sorts of optical vortices (Rafighdoost and Sabatyan 2016). In recent years, several papers have examined the creation of a laser beam with phase singularities (Khonina et al 1992;Saad et al 2016;Ebrahim et al 2017;Nossir et al 2021;Belafhal and Nebdi 2014;Belafhal and Saad 2017;Chib et al 2023a;Chib et al 2023b;El Halba et al 2022;El Halba et al 2017;Ebrahim et al 2022). In 2016, Sabatyan et al (Sabatyan et al 2016) are treated the generation of the square array of optical vortices by a multiregional spiral square zone plate (MRSSZP), which is subdivided into a few regions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was recently revealed that, by means of a spiral orthogonal zone plate, one may employ different sorts of optical vortices (Rafighdoost and Sabatyan 2016). In recent years, several papers have examined the creation of a laser beam with phase singularities (Khonina et al 1992;Saad et al 2016;Ebrahim et al 2017;Nossir et al 2021;Belafhal and Nebdi 2014;Belafhal and Saad 2017;Chib et al 2023a;Chib et al 2023b;El Halba et al 2022;El Halba et al 2017;Ebrahim et al 2022). In 2016, Sabatyan et al (Sabatyan et al 2016) are treated the generation of the square array of optical vortices by a multiregional spiral square zone plate (MRSSZP), which is subdivided into a few regions.…”
Section: Introductionmentioning
confidence: 99%